SISTEM PENDUKUNG KEPUTUSAN TERHADAP IMPLEMENTASI BELAJAR SISWA E-LEARNING UNTUK MENENTUKAN PENGEMBANGAN BELAJAR PADA SMK PUSTEK SERPONG - Sudaryono Sudaryono; Untung Rahardja; Herva Emilda Sari (LPPM Unbaja, 2019)
The development of increasingly advanced technology, especially computers that have entered various types of fields, one of them is the field of information using E-Learning learning. The internet is a way to get and deliver learning information quickly, wherever and whenever. This can be best utilized in the teaching and learning process using the E-Learning class method for an educational institution to minimize delays in the delivery of information, and as a basis for providing the best service for the quality of learning for students. In order to realize learning achievement, a development must be carried out in the process of learning activities for students to master the teaching materials provided by the teacher in school. In its improvement, it takes the development of learning methods and supporting decision-making in learning outcomes that can develop improvements in catching power, ways of learning, thinking of students, and the catching value of the material they get from the teacher, where this is found in the development of E-Learning class learning models . Students can learn and interact about instructional materials, difficulties that occur in schools using web-site media in pleasant internet access, flexible time, and students have a high appeal for the interest in learning to use E-Learning classes. The method chosen to solve problems with many criteria is SAW Simple Additive Weighting, one method that can be used to solve existing problems. This method is chosen because it can determine the weights for each attribute, followed by an alternative ranking that will be used as a decision making for student learning outcomes using E-learning.